Developing auto-inducible Pgrac57 promoter in Bacillus subtilis - Phan , Thi Phương Trang; Tran , Thi Anh Dao; Truong , Thi Lan Lan; Nguyen , Thuy Mỹ Linh; Au , Thi Hanh; Nguyen , Duc Hoang (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
Bacillus subtilis has many advantages such as: safe, non-pathogenic, endotoxin-free features. Therefore, B. subtilis has been widely ultilized in therapeutic proteins and important industrial enzymes production. Over the last few years, the potential application of B. subtilis for recombinant proteins synthesis has been significantly enhanced by using pHT - vector system with Pgrac promoter. In this study, we developed inducer-free expression vector for B. subitlis based on Pgrac57 promoter and used GFP protein as a reporter. The results showed that we successfully constructed inducer-free vector pHT1686 with Pgrac57 promoters. These vectors are totally able to express GFP protein without any inducer in B. subtilis strain 1012. Moreover, GFP expression level reached 11% of the total cellular proteins. Additionally, GFP activities are in the same range with the inducer-free vector.